An Audit of Indications, Complications, and Justification of Hysterectomies at a Teaching Hospital in India - Pandey, Deeksha; Sehgal, Kriti; Saxena, Aashish; Hebbar, Shripad; Nambiar, Jayaram; Bhat, Rajeshwari G. (International Journal of Reproductive Medicine, 2014)
Objective. Aim of this audit was to analyze indications, complications, and correlation of preoperative diagnosis with final histopathology report of all hysterectomies, performed in a premier teaching hospital. Methods. Present study involved all patients who underwent hysterectomy at a premier university hospital in Southern India, in one year (from 1 January, 2012, to 31 December, 2012). Results. Most common surgical approach was abdominal (74.7%), followed by vaginal (17.8%), and laparoscopic (6.6%) hysterectomy. Most common indication for hysterectomy was symptomatic fibroid uterus (39.9%), followed by uterovaginal prolapse (16.3%). Overall complication rate was 8.5%. Around 84% had the same pathology as suspected preoperatively. Only 6 (5 with preoperative diagnosis of abnormal uterine bleeding and one with high grade premalignant cervical lesion) had no significant pathology in their hysterectomy specimen. Conclusion. Hysterectomy is used commonly to improve the quality of life; however at times it is a lifesaving procedure. As any surgical procedure is associated with a risk of complications, the indication should be carefully evaluated. With the emergence of many conservative approaches to deal with benign gynecological conditions, it is prudent to discuss available options with the patient before taking a direct decision of surgically removing her uterus.